1993
DOI: 10.1080/09515079308254500
|View full text |Cite
|
Sign up to set email alerts
|

Counsellor verbal response mode usage and client-perceived rapport

Abstract: The effects of usage of eight verbal response modes by trainee counsellors during an initial interview were determined by reference to client-perceived rapport. Data on rapport were gathered via a standardized client's minute-by-minute ratings of his experience of rapport on a five-point scale during the interview. A total of ten counselling interviews were conducted, and data were examinedfor overall effects (i.e. during the interview as a whole) and minute-by-minute effects. Restatements, Minimal Encouragers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…As for the second question, several investigations have been conducted into effects of microcounseling training on client outcomes. Sharpley and Guiddara (1993) found that high client ratings of counsellors were associated with the adequate use of microskills. Other studies found high positive correlations between the adequate use of microskills and patient satisfaction (Bensing, 1991; Bensing & Dronkers, 1988; Bögels, 1994), patient self‐disclosure in a diagnostic interview (Verhaak, 1988) and establishing a credible relationship with clients (Toriello & Strohmer, 2004).…”
Section: Discussionmentioning
confidence: 98%
“…As for the second question, several investigations have been conducted into effects of microcounseling training on client outcomes. Sharpley and Guiddara (1993) found that high client ratings of counsellors were associated with the adequate use of microskills. Other studies found high positive correlations between the adequate use of microskills and patient satisfaction (Bensing, 1991; Bensing & Dronkers, 1988; Bögels, 1994), patient self‐disclosure in a diagnostic interview (Verhaak, 1988) and establishing a credible relationship with clients (Toriello & Strohmer, 2004).…”
Section: Discussionmentioning
confidence: 98%
“…The results showed that a humanitarian interviewing style significantly predicted a better WA between interviewer and interviewee, whereas a dominant interviewing style was predictive of a poorer WA. WA has been used synonymously with rapport (Sharpley & Guidara, 1993;Sharpley, Guidara, & Rowley, 1994), and both constructs share the development of bonds as a common aim in communicative interaction (Altman, 1990;Andrusyna, Tang, DeRubeis, & Luborsky, 2001;Argyle, 1990;Busseri & Tyler, 2003;Horvath, 2001). Tickle-Degnen (2002) argues that rapport is similar to WA and is a prerequisite for its development.…”
Section: Rapport Operationalized As a Humanitarianmentioning
confidence: 97%
“…Most similarities can be found between rapport and one of the components of the working alliance: an emotional bond (Sharpley & Ridgway, ; Sharpley et al , ). These two terms have even been used synonymously (Sharpley, Guidara, & Rowley, ; Sharpley & Guidara, ), and they overlap both on a conceptual level and in terms of measurement. Studies concerning rapport (both before and after the publication of the framework by Tickle‐Degnen and Rosenthal ()) adopt the bond scale from the WAI (Horvath & Greenberg, ) to measure rapport (post‐session measurement), in some cases combined with a comparison to an in‐session measurement using another scale (Sharpley & Ridgway, ; Sharpley et al , ).…”
Section: Introductionmentioning
confidence: 99%